Investigation Effects of the Controller Performance of DFIG on its Inertia Response (Global Journals of Research in Engineering, 2011)
Inertia response is the first reaction of the generator to the frequency disturbance in power system that is so important for the grid. Conventional synchronous generators have a high inertia response inherently and therefore the power system by these generators has a high Inertia response. Recently, using the wind turbines by DFIG generators are become popular,consequently, investigation the Inertia response of DFIG is important. At this work the inertia response of a DFIG that is connected to an infinite bus investigated and it is observed that DFIG has a very low inertia response, because its controller takes the slip of machine within fix range.In this paper for studying on effect of the operation speed of the DFIG controller on its inertia response, several different times took for its controller speed.